Retinal dysfunction in Huntington’s disease mouse models concurs with local gliosis and microglia activation - Fátima Cano-Cano; Francisco Martín-Loro; Andrea Gallardo-Orihuela; María del Carmen González-Montelongo; Samanta Ortuño-Miquel; Irati Hervás-Corpión; Pedro de la Villa; Lucía Ramón-Marco; Jorge Navarro-Calvo; Laura Gómez-Jaramillo; Ana I. Arroba; Luis M. Valor (Scientific Reports, 2024)
Abstract Huntington’s disease (HD) is caused by an aberrant expansion of CAG repeats in the HTT gene that mainly affects basal ganglia. Although striatal dysfunction has been widely studied in HD mouse models, other brain areas can also be relevant to the pathology. In this sense, we have special interest on the retina as this is the most exposed part of the central nervous system that enable health monitoring of patients using noninvasive techniques. To establish the retina as an appropriate tissue for HD studies, we need to correlate the retinal alterations with those in the inner brain, i.e., striatum. We confirmed the malfunction of the transgenic R6/1 retinas, which underwent a rearrangement of their transcriptome as extensive as in the striatum. Although tissue-enriched genes were downregulated in both areas, a neuroinflammation signature was only clearly induced in the R6/1 retina in which the observed glial activation was reminiscent of the situation in HD patient’s brains. The retinal neuroinflammation was confirmed in the slow progressive knock-in zQ175 strain. Overall, these results demonstrated the suitability of the mouse retina as a research model for HD and its associated glial activation.